Isolation and structural elucidation of a low-molecular-weight polysaccharide from the roots of Panax ginseng C. A. Meyer. Issue 2 (17th January 2022) - Zhao, Bin; Wang, Xin-Ying; Luo, Wen; Lin, Yue; Lv, Chong-Ning; Lu, Jin-Cai
Abstract: A low-molecular-weight polysaccharide named MCGP-L was extracted and purified from the roots of Mountain cultivated ginseng ( Panax ginseng C. A. Meyer). The polysaccharide MCGP-L was purified by molecular exclusion chromatography using the Sephadex G-25 column. The average molecular weight of MCGP-L was estimated to be 3 × 10 3  kDa. Monosaccharide composition analysis showed MCGP-L was composed of three kinds of monosaccharide: D-glucose, D-galactose and D-mannose. The physicochemical properties and structural characteristics of MCGP-L were investigated by the combination of chemical and instrumental analysis such as methylation analysis, High Performance Gel-Permeation Chromatography (HPGPC), High Performance Liquid Chromatography (HPLC) and Nuclear Magnetic Resonance (NMR). The backbone of MCGP-L was composed of (1→4)-linked-α-D-Glc p residues and with branch chain substituted at O -6 position of (1→4, 6)-linked-α-D-Glc p . The branch chain consists of →6)-α-D-Gal p -(1→, →2)-α-D-Man p -(1→ and β-D-Glc p -(1→. Graphical Abstract: UF0001